2020
DOI: 10.1002/jcp.29844
|View full text |Cite
|
Sign up to set email alerts
|

Low shear stress regulates vascular endothelial cell pyroptosis through miR‐181b‐5p/STAT‐3 axis

Abstract: Low shear stress and pyroptosis both play an important role in the onset and development of atherosclerosis (AS). MicroRNAs (miRNAs) are a kind of short (18-22) nucleotide sequences that can bind to the 3′-untranslated region (3′-UTR) of messenger RNA, thereby regulating programmed cell death including pyroptosis. How

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 31 publications
1
21
0
2
Order By: Relevance
“…As an important triggering factor and endogenous regulator of cardiovascular in ammation, pyroptosis not only induces the death of endothelial cells but also leads to enhanced endothelium permeability, promotes the expression of endothelial cell-adhesion molecules, recruits monocytes and promotes their differentiation into macrophages, and aggravates blood vessel damage [42][43][44]. Studies have shown that the pyroptosis regulated by the NLRP3 in ammasome is closely related to the progression of cardiovascular disease [43,45]. It has been shown that GDF11 exerts a cardioprotective effect by inhibiting the cardiomyocyte pyroptosis induced by the NLRP3 in ammasome [15].…”
Section: Discussionmentioning
confidence: 99%
“…As an important triggering factor and endogenous regulator of cardiovascular in ammation, pyroptosis not only induces the death of endothelial cells but also leads to enhanced endothelium permeability, promotes the expression of endothelial cell-adhesion molecules, recruits monocytes and promotes their differentiation into macrophages, and aggravates blood vessel damage [42][43][44]. Studies have shown that the pyroptosis regulated by the NLRP3 in ammasome is closely related to the progression of cardiovascular disease [43,45]. It has been shown that GDF11 exerts a cardioprotective effect by inhibiting the cardiomyocyte pyroptosis induced by the NLRP3 in ammasome [15].…”
Section: Discussionmentioning
confidence: 99%
“…Low shear stress plays a critical role in the development of atherosclerosis. Regulation of miR181b‐5p and transcriptional activation factor 3 (STAT‐3) expression induces NLRP3‐dependent pyroptosis (X. Xu et al, 2020).…”
Section: Role Of Pyroptosis In Atherosclerosismentioning
confidence: 99%
“…77 In addition to ox-LDL, shear stress changes caused by abnormal blood flow are an important factor in atherosclerosis and low fluid shear stress is conducive to the occurrence of atherosclerosis and plate growth. Xu et al 78 reported that low shear stress can downregulate mechanosensitive miR-181-5p expression and induce pyroptosis in HUVECs. Moreover, miR-181-5p mimic transfection can suppress signal transduction and transcriptional activation factor 3 (STAT3) gene expression by directly binding to its 3 0 UTR, resulting in reduced NLRP3 transcription through lysine deacetylation and amelioration of NLRP3 inflammasome-dependent pyroptosis.…”
Section: Atherosclerosismentioning
confidence: 99%
“…Moreover, miR-181-5p mimic transfection can suppress signal transduction and transcriptional activation factor 3 (STAT3) gene expression by directly binding to its 3 0 UTR, resulting in reduced NLRP3 transcription through lysine deacetylation and amelioration of NLRP3 inflammasome-dependent pyroptosis. 78 lncRNAs Intragastric administration of melatonin decreases expression of the pyroptosis-associated genes NLRP3, ASC, cleaved caspase-1, NF-kB/GSDMD, and GSDMD N-termini and markedly reduces atherosclerotic plaques in high-fat diet-treated ApoE À/À mouse aortas. 79 Mechanistically, melatonin downregulates lncRNA MEG3, high expression of which enhances pyroptosis in HAECs.…”
Section: Atherosclerosismentioning
confidence: 99%